Mn 3d bands and Y–O hybridization of hexagonal and orthorhombic YMnO3 thin films. (13th June 2017) - Martins, H P; Mossanek, R J O; Martí, X; Sánchez, F; Fontcuberta, J; Abbate, M
Abstract: We report here the O K -edge x-ray absorption spectra of hexagonal and orthorhombic YMnO3 thin films, aiming at comparing the changes in the Mn 3 d bands as well as the role of Y 4 d –O 2 p hybridization. The experimental results were analyzed using first principles (GGA) band structure calculations. The spectra present clear differences in the Mn 3 d bands, which are attributed to changes in the Mn-O coordination and symmetry. A strong Y 4 d –O 2 p hybridization is observed in both the hexagonal and orthorhombic films, and its possible role on the occurrence of the observed ferroelectricity is discussed.